Confronting a Compound Crisis: The School Principal’s Role During Initial Phase of the COVID-19 Pandemic - Reyes-Guerra, Daniel; Maslin-Ostrowski, Patricia; Barakat, Maysaa Y.; Stefanovic, Melanie Ann (Frontiers in Education, 2021)
The COVID-19 pandemic, bringing to the forefront and catalyzing long-unconfronted racial and economic inequities, in addition to economic collapse and deep political divisions - which all impact students and schools – has resulted in a compound crisis requiring a novel conceptualization of school leadership during times of crisis. This qualitative study captures the leadership experience of principals during the apocalyptic crisis _ the COVID-19 pandemic - beginning from the time schools were closing in March 2020 to the end of the school year in June. Crisis leadership, transformative leadership and social capital constitute the overarching framework for this study. The purpose of this case study was to discover how principals engaged in their thinking and practice to handle the compound crisis, in order to generate a rich description and gain an understanding of school leadership during the first phase of the COVID 19 pandemic. Our research questions were: What were the challenges and complications of leading during the initial phase of the compound crisis from the perspective of principals? How did principals respond? What were the emergent leadership practices? For this case study, we used a purposeful, maximum variation sample of nine principals in Florida. We sought balance in gender, race and ethnicity, and grade level. In-depth interviews were conducted using a structured protocol. Analysis treated each principal as an individual case, then cross-case thematic analysis was employed to uncover common patterns and themes. Three findings emerged. First, participants drew upon their individual reservoirs of shared leader qualities, including personalized and pragmatic communicator; leading with flexibility, creativity and care; bending rules and shifting priorities; and showing resilience under pressure. Second, they tapped into their schools’ strengths, including school context and in-house expertise. Third, they made inter-school connections. The first phase of the compound crisis pushed principals to prioritize care, safety, and wellbeing of students, teachers, and communities above accountability measures and systemic institutional constraints. A call to action for equity is the next logical step for system consideration, and was echoed by participating principals, as well as a realization that going back to old ways is no longer an option.